This bridge called my back: Writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press., 2015)
merged in the last quarter of the twentieth century. Through personal essays, criticism, interviews, testimonials, poetry, and visual art, the collection explores, as coeditor Cherríe Moraga writes, the complex confluence of identities–race, class, gender, and sexuality–systemic to women of color oppression and liberation. Reissued here, forty years after its inception, this anniversary edition contains a new preface by Moraga reflecting on Bridge's living legacy and the broader community of women of color activists, writers, and artists whose enduring contributions dovetail with its radical vision. Further features help set the volume's historical context, including an extended introduction by Moraga from the 2015 edition, a statement written by Gloria Anzaldúa in 1983, and visual art produced during the same period by Betye Saar, Ana Mendieta, Yolanda López, and others, curated by their contemporary, artist Celia Herrera Rodríguez. Bridge continues to reflect an evolving definition of feminism, one that can effectively adapt to and help inform an understanding of the changing economic and social conditions of women of color in the United States and throughout the world.
Première édition 1981. Les textes "La Guëra" de Cherríe L. Moraga et « Lesbianism As an Act of Resistance » de Clark, Cherryl ont été donné en lecture au cours POL4212.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* de couleur; histoire et politique; intersectionnalité; lit3220; littérature; pol4212; pratiques féministes; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; témoignage; états-unis; études littéraires

« Réfugiées d’un monde en feu ». Avant-propos à la deuxième édition, 1983 - Moraga, Cherríe L. (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Trois années sont passées et j’essaie de m’imaginer à quoi ressemble la nouvelle lectrice ou le nouveau lecteur de Bridge. Qu’avez-vous besoin de savoir ? J’ai entendu à travers des lettres et lors de mes voyages, que le livre avait aidé à changer l’esprit de certaines personnes (et, je l’espère, également leur cœur), mais personne n’aura été plus transformé par ce livre que les femmes ayant contribué à son existence. Il a provoqué un changement tellement fondamental dans ma vie qu’aujourd’hu...
Keywords: amériques; approches et analyses; cours; fem1300; féminisme décolonial; inégalités; premier cycle; queer; racisme; ressource en ligne; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; violences